Intranasal administration of dauricine loaded on graphene oxide: multi-target therapy for Alzheimer's disease - Kaixuan Wang; Lingfeng Wang; Ling Chen; Chiwei Peng; Beijiao Luo; Jingxin Mo; Wei Chen (Taylor & Francis Group, 2021)
Alzheimer's disease (AD) is a degenerative disease of the central nervous system characterized by progressive cognitive and memory-related impairment. However, current therapeutic treatments have not proved sufficiently effective, mainly due to the complicated pathogenesis of the disease. In this study, a nano-formulation of graphene oxide (GO) loaded with dauricine (Dau) was investigated in terms of the combined anti-inflammatory and anti-oxidative stress effects of Dau and the inhibition of misfolding and aggregation of the amyloid-β (Aβ) protein by GO. Both in vivo and in vitro models were induced using Aβ1-42, and the formulation was administered nasally in mice. The results showed that GO loaded with Dau greatly reduced oxidative stress through increasing superoxide dismutase levels and decreasing reactive oxygen species and malondialdehyde levels in vitro; it also alleviated the cognitive memory deficits and brain glial cell activation in mice with Aβ1-42-induced AD. This proved that GO loaded with Dau could protect against Aβ1-42-induced oxidative damage and apoptosis in both in vitro and in vivo AD models; therefore, GO loaded with Dau has the potential to be an effective and agent for the rapid treatment of AD.